Familiar del3p syndrome: The uncertainty of the prognosis. A case report. Issue 4 (9th March 2021) - Martins, Márcia; Arantes, Regina; Botelho, Pedro; Souto, Marta; Moutinho, Osvaldo; Pinto Leite, Rosário
Abstract: The 3p deletion syndrome is an unusual condition. The few cases described are mainly de novo. We described a familial case detected in a prenatal diagnosis. Three members of the family had the 3p26.3‐p26.1 deletion; however, only the son presented clinical features. Abstract : The 3p deletion syndrome is an unusual condition. The few cases described are mainly de novo. We described a familial case detected in a prenatal diagnosis. Three members of the family had the 3p26.3‐p26.1 deletion; however, only the son presented clinical features.